Pengaruh Rasio Keuangan dan Kebijakan Dividen Terhadap Perubahan Laba Perusahaan di Indonesia pada Masa Pandemi Covid-19 - Sumitro, Daffa Putra Kedua; Ulupui, I Gusti Ketut Agung; Nasution, Hafifah (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
This study aims to determine the effect of financial ratios and dividend policy on changes in corporate profits in Indonesia during the COVID-19 pandemic. The financial ratios used as variables in this study are profitability ratios, liquidity ratios, and solvency ratios, which are measured by Net Profit Margin, Current Ratio, and Debt to Asset Ratio. While the Dividend Policy is measured by the Dividend Payout Ratio. This study makes all non-financial sector companies listed on the Indonesia Stock Exchange (IDX) in 2020 as the population. The sample in this study amounted to 113 companies obtained through purposive sampling technique. The analyticaltechnique used in this study is multiple linear regression analysis, with secondary data types processed using the IBM SPSS version 25 application. The results of this study indicate that Net Profit Margin has a positive effect on changes in company profits, Current Ratio and Debt to Asset Ratio has no effect on changes in company profits, while Dividend Policy has a negative effect on changes in company profits.